2022
DOI: 10.1038/s43587-022-00308-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual identity of enterocytes regulates autophagy to determine intestinal health, lifespan and responses to rapamycin

Abstract: Pharmacological attenuation of mTOR presents a promising route for delay of age-related disease. Here we show that treatment of Drosophila with the mTOR inhibitor rapamycin extends lifespan in females, but not in males. Female-specific, age-related gut pathology is markedly slowed by rapamycin treatment, mediated by increased autophagy. Treatment increases enterocyte autophagy in females, via the H3/H4 histone-Bchs axis, whereas males show high basal levels of enterocyte autophagy that are not increased by rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…The Drosophila intestine plays a crucial role in TOR-dependent longevity 11 , 29 32 . Treating flies with Rapa improved gut health by increasing intestinal autophagy, reducing intestinal stem cell (ISC) turnover, age-related gut dysplasia and leakiness 11 , 29 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Drosophila intestine plays a crucial role in TOR-dependent longevity 11 , 29 32 . Treating flies with Rapa improved gut health by increasing intestinal autophagy, reducing intestinal stem cell (ISC) turnover, age-related gut dysplasia and leakiness 11 , 29 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Rapa treatment or the removal of S6K prolongs the lifespan of female animals more than males 4 , 16 , 32 , suggesting an evolutionarily conserved, sexually dimorphic aspect of longevity mechanisms. In line with the observation that genes related to the noncanonical NF-κB pathway are more abundant in the aged livers of female mice compared to male mice 76 , we have noted relatively higher levels of inflammaging in fat bodies of female flies compared to males, which can be further mitigated by inhibiting TORC1–S6K signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in flies and mice have demonstrated that inhibition of mTORC1 with rapamycin is also associated with elevated H3 and H4 levels. 63 , 64 , 65 Therefore, increased histone levels and altered chromatin organization are likely a general phenomenon of metabolic remodeling. Given that overexpression of histones also promotes tissue health and longevity, it will be interesting to ascertain the extent to which these effects are mediated by potentiated HSF1 activity and enhanced proteostasis capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, research on ageing using model organisms has considered both lifespan (as measured by survival) and healthspan (as measured by changes in behaviour and other phenotypes with age) (Le Bourg, 2020). Drosophila has been a productive model system for investigating sex differences in both lifespan and healthspan, as well as the sex-specific plasticity of these phenotypes with longevity-promoting interventions (Regan et al, 2016(Regan et al, , 2022. With respect to lifespan, my current results are consistent with many of these past studies: in each strain investigated, I observed significantly greater longevity in female compared to male flies (Figure 1).…”
Section: Discussionmentioning
confidence: 99%